21 Implementing team based care to improve cervical cancer screening rate in community based resident run clinic. (2nd December 2020) - Sohail, Momena; Fayyaz, Fatima; Finlay, Sarah; Affnan, Ammar
Abstract : Background: In 2015, for every 100, 000 women, 8 new Cervical Cancer cases were reported and 2 died of cancer. The introduction of effective screening has led to a steady decrease in Invasive Cervical Cancer incidence and mortality in high-income countries however Socioeconomic status and access to health have created a cervical cancer disparity gap. This QI project was undertaken to evaluate and improve cervical cancer screening rates at a community-based resident-run IM clinic. Objectives: Increase screening rate to 50% by Dec 2018 and sustain increase rates to above 45% in all months in 2019. Methods: At the start of 2018, physician data reported that screening rates at the clinic were 36%, lower than those of our other clinical practices. A clinical survey was completed to assess patient understanding of cervical cancer screening. The first intervention was sharing individual provider data with the residents. This was a weak intervention and did not improve rates of screening. Our second intervention was a team-based approach and pre-visit planning: identify patients and calling them1–2 days ahead and including PAP in the daily huddle. Results: The original survey showed that out of 124 women, 66 needed screening. Surveys intensified lack of continuity; several listed PCPs were not seeing their own patients, patients unsure of resources, and financial concerns as barriers. The team-based approach showed that more PAPs were being done per week, and was streamlined with staff feedback to minimize disruption to current workflow. With a goal of 50% by the end of 2018, we were able to achieve 48.9% screening rates. The increase was sustained above 45% in 8/12 months in 2019 (figure 1 ). Conclusions: Team-based practice is an effective practice in increasing cervical cancer screening to overcome challenges in continuity of care, health access disparity, and resource allocation in a primary care clinic.